2018
DOI: 10.1111/acer.13574
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure Increases Histamine H3 Receptor‐Mediated Inhibition of Glutamatergic Neurotransmission in Rat Dentate Gyrus

Abstract: These results suggest that a PAE-induced elevation in H receptor-mediated inhibition of glutamate release from perforant path terminals as 1 mechanism contributing the LTP deficits previously observed in the dentate gyrus of PAE rats, as well as providing a mechanistic basis for the efficacy of H receptor inverse agonists for ameliorating these deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Rate remapping by CA3 place cells, which was reduced in the present study, is dependent on the integrity of synaptic plasticity and NMDA receptor function at perforant pathway synapses [37]. Previous studies have also reported that moderate PAE can reduce mGluR5 receptor function in the dentate gyrus [85] and leads to elevated histamine H3-receptor-mediated inhibition of glutamate release from perforant path nerve terminals [86]. Likewise, the integrity of input from the entorhinal cortex, which forms the most prominent source of perforant path axons, is critical for place cell activity [87], and damage to entorhinal cortical cells can produce a similar loss of place field stability and reduction in spatial tuning [88][89][90].…”
Section: Discussionsupporting
confidence: 57%
“…Rate remapping by CA3 place cells, which was reduced in the present study, is dependent on the integrity of synaptic plasticity and NMDA receptor function at perforant pathway synapses [37]. Previous studies have also reported that moderate PAE can reduce mGluR5 receptor function in the dentate gyrus [85] and leads to elevated histamine H3-receptor-mediated inhibition of glutamate release from perforant path nerve terminals [86]. Likewise, the integrity of input from the entorhinal cortex, which forms the most prominent source of perforant path axons, is critical for place cell activity [87], and damage to entorhinal cortical cells can produce a similar loss of place field stability and reduction in spatial tuning [88][89][90].…”
Section: Discussionsupporting
confidence: 57%
“…PAE is associated with widespread abnormalities in brain structure and function. Among these are changes to white matter integrity (Wozniak et al, 2011), cortical thickness (Yang et al, 2012), receptor expression (Galindo et al, 2004), neurotransmission (Varaschin et al, 2018), long-term potentiation (Sutherland et al, 1997), and structural synaptic plasticity (Rice et al, 2012), which could potentially explain changes in network properties, but are not accessible in the present investigation. Measures of path length and global efficiency have also been associated with genetic heritability (van den Heuvel et al, 2013, Fornito et al, 2011, and PAE is known to influence multiple epigenetic mechanisms that affect brain development (Lussier et al, 2017), which represent additional routes by which PAE can alter network characteristics.…”
Section: Global Measures Of Network Modularity Have Not Been Previouslymentioning
confidence: 91%
“…Radio-histochemical studies employing the selective H3R antagonist [ 3 H]-A349821 indicated that moderate PAE did not affect H3R density in any brain region measured ( Varaschin et al, 2018 ). However, using the selective H3R agonist methimepip to stimulate [ 35 S]-GTPγS (GTP) binding as a measure of H3R receptor-effector coupling, we observed a significant enhancement of GTP binding in hippocampal and cerebrocortical regions of PAE rats, particularly at higher agonist concentrations ( Varaschin et al, 2018 ). The functional significance of this heightened H3 receptor-effector coupling response in PAE rats was examined in dentate gyrus slices.…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of this heightened H3 receptor-effector coupling response in PAE rats was examined in dentate gyrus slices. The ability of methimepip to decrease the probability of glutamate release from dentate gyrus slices, noted as an increase in the paired-pulse ratio measure, was significantly elevated in PAE rats ( Varaschin et al, 2018 ). Further, the concentrations of methimepip that lowered the probability of glutamate release were similar to the methimepip concentrations that enhanced GTP binding in dentate gyrus of PAE rats.…”
Section: Introductionmentioning
confidence: 99%